Analysis of the D+→K−π+e+νe decay channel - Amo Sanchez, Pablo del; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
Using 347.5 fb−1 of data recorded by the BABAR detector at the PEP-II electron-positron collider, 244×103 signal events for the D+→K−π+e+νe decay channel are analyzed. This decay mode is dominated by the K[bar]∗(892)0 contribution. We determine the K[bar]∗(892)0 parameters: mK∗(892)0=(895.4±0.2±0.2) MeV/c2, Γ0K∗(892)0=(46.5±0.3±0.2) MeV/c2, and the Blatt-Weisskopf parameter rBW=2.1±0.5±0.5 (GeV/c)−1, where the first uncertainty comes from statistics and the second from systematic uncertainties. We also measure the parameters defining the corresponding hadronic form factors at q2=0 (rV=V(0)A1(0)=1.463±0.017±0.031, r2=A2(0)A1(0)=0.801±0.020±0.020) and the value of the axial-vector pole mass parametrizing the q2 variation of A1 and A2: mA=(2.63±0.10±0.13) GeV/c2. The S-wave fraction is equal to (5.79±0.16±0.15)%. Other signal components correspond to fractions below 1%. Using the D+→K−π+π+ channel as a normalization, we measure the D+ semileptonic branching fraction: B(D+→K−π+e+νe)=(4.00±0.03±0.04±0.09)×10−2, where the third uncertainty comes from external inputs. We then obtain the value of the hadronic form factor A1 at q2=0: A1(0)=0.6200±0.0056±0.0065±0.0071. Fixing the P-wave parameters, we measure the phase of the S wave for several values of the Kπ mass. These results confirm those obtained with Kπ production at small momentum transfer in fixed target experiments.
*BABAR Collaboration: P. del Amo Sanchez, J. Marks, U. Uwer [und 434 weitere Personen]
Im Titel ist das Plus- und das Minuszeichen hochgestellt
Im Titel ist der zweite Buchstabe "e" tiefgestellt
Gesehen am 05.10.2022